EVALUACIÓN DEL TIPO DE ENVASE EN EL PERÍODO DE ALMACENAMIENTO Y EL DETERIORO EN LAS CARACTERÍSTICAS FÍSICAS Y SENSORIALES DE LA SALCHICHA Y CHORIZO CON QUINUA GERMINADA (Chenopodium quinoa) - Rodríguez Rivera, Roger Steven (2023)
The present investigation evaluated the type of packaging in the storage time and the deterioration of the physical and sensory characteristics of the sausage and chorizo made from sprouted Quinoa (Chenopodium quinoa) flour, considering two types of packaging: vacuum packaging and ziploc packaging. For the development of this research, the two best treatments from previous research were taken (Evaluation of sprouted quinoa flour (Chenopodium quinoa) as an emulsifying and texturizing agent in the production of type 3 sausage. And Evaluation of quinoa flour (Chenopodium quinoa Willd) germinated as an emulsifying and texturizing agent in the preparation of smoked chorizo). A bifactorial A*B+1 design was used, together with a completely randomized design plus a control. Where the factors were: Factor A= type of packaging (a0 empty and a1 ziploc), Factor B= days of storage (b0 9 days, b1 15 days, b2 30 days). Obtaining a total of 6 treatments that were replicated by 3, plus a control considering a total of 21 experimental units. Considering the bromatological characteristics of sprouted quinoa flour sausage and chorizo. In relation to the sensory analysis, the significance tests were carried out with a Tukey test (p ≤ 0.05) where the treatment a0b1 (empty + 15 days) was evidenced, which represented the best results in its organoleptic characteristics, in the same way. way it stood out in flavor over all treatments. Complying with the parameters established in the INEN 1338 standard, maintaining its safety, and considering it suitable for the consumer.